Necesidad de incluir como contraventor al propietario del vehículo automotor que circule con neumáticos que superen el límite de desgaste reglamentario. - Chiriboga Vivanco, Luis Alejandro (2015)
The present investigative work has as objective, to reform the breach tipificada in the article 383 of the Code Organic Penal Integral (COIP), sanctioning as responsible solidary, to the proprietor of the vehicle, to cooperate in the neglect of the prohibition prepared in the article 172 of the Regulation Organic law of Transport Land I Traffic and security vial (RLOTTTSV), taking like sample the breaches happened in the county of The Gold, in the years 2010 and 2013. For the effect the technique that allowed us recabar the information was the interview that was applied a provincial director of the commission of terrestrial transport, traffic - security vial, the provincial boss of the traffic police, policemen of traffics and professional chauffeurs that I form an universe of 100 people. With this information you proceeded to elaborate the statistical squares with their respective graphics, carrying out the interpretation of each one of them, ended this with the writing of the summations and recommendations, opening the way to the proposal, which is modification of the article 383 of Code Organic Penal Integral (COIP), so that in their content it is included the proprietor of the railcar as responsible solidary of the infraction tipificada in this article.